Implementation of integrated pest control to reduce rhino beetle (Oryctes rhinoceros) attacks in oil palm plantations - Idum Satia Santi; Alfi Prayoga; Heri Setyawan; Wandha Atmaka Aji (Tropical Plantation Journal, 2022)
Oryctes rhinoceros or Rhino beetle ( Coleoptera; Scarabidae) is a major pest in oil palm plantations. This pest is very harmful, especially in replanting areas, and young plants cause up to 25 per cent of palm oil-related deaths. This study aims to evaluate the effectiveness of integrated pest management in suppressing the population and development of O. rhinoceros. The research was conducted at the Oil Palm Plantation, PT. Sumber Indah Perkasa, Penawartama, Tulangbawang Regency, Lampung Provincial for one year. The analysis used is a descriptive analysis involving the collection of data from a variety of control techniques. The results showed that the pest control techniques of O. rhinoceros lightrap, ferotrap, holetrap, nets, larval quotes and chemistry could suppress or decrease pest populations. The control with light traps is very efficient because it obtained the number of captures of imago beetles up to 246,224 in 1 year. The integrated pest control of O. rhinoceros successfully reduced the attack of beetles until it did not reach the economic threshold. It is hoped that implementing integrated O. rhinoceros pest control can be a reference for plantations